2015
DOI: 10.4236/ojneph.2015.51001
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Treatment for Uremic Pruritus

Abstract: This review highlights recent advances in pathophysiology and treatment for uremic pruritus, especially focusing on various interventions. Pruritus in patients on hemodialysis (HD) and peritoneal dialysis (PD) still remains an unresolved issue. Recently, the efficacy and safety of nalfurafine hydrochloride have been reported in Japan, and at present, more than thirty thousand patients receive this new drug. In comparison with the efficacy of this new drug, acupuncture, a form of traditional Japanese therapy, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
1
17
0
2
Order By: Relevance
“…Twenty-five per cent of patients with uraemic pruritus experience exacerbated symptoms during or after dialysis (Keithi-Reddy et al 2007). Pruritus in patients on haemodialysis and peritoneal dialysis still remains an unresolved issue (Suzuki et al 2015). In a longitudinal study, 84% of 103 patients receiving haemodialysis reported itching on a daily or nearly daily basis.…”
Section: Uraemic Pruritusmentioning
confidence: 99%
“…Twenty-five per cent of patients with uraemic pruritus experience exacerbated symptoms during or after dialysis (Keithi-Reddy et al 2007). Pruritus in patients on haemodialysis and peritoneal dialysis still remains an unresolved issue (Suzuki et al 2015). In a longitudinal study, 84% of 103 patients receiving haemodialysis reported itching on a daily or nearly daily basis.…”
Section: Uraemic Pruritusmentioning
confidence: 99%
“…As reported, chronic renal failure induce the most commonly systemic pruritus (6). The incidence of pruritus in chronic renal failure is 42% and in patients with hemodialysis, 90% (7), of which 52.5% of the patients had the most severe feeling of itching during dialysis (8). Accordingly, although access to hemodialysis has been shown to maintain and sustain the chronic renal failure of patients' survival and improve the general health, it has increased the number of patients with itching (5).…”
Section: Contextmentioning
confidence: 99%
“…However, various hypotheses have been proposed to justify it: release of histamine from mast cells and basophils, dryness and skin atrophy, proliferation of skin mast cells, atrophy of skin fat cells, electrolyte imbalances and the accumulation of bile acids, anemia, increased skin pH and hyperparathyroidism (10), opioids, hypersensitivity to hemodialysis solution (11), and high levels of interleukin 2 (12). Considering that the highest severity of itching has been reported during hemodialysis (8); itching during hemodialysis may be due to inflammatory mediators such as IL-I, which is released in response to plasma C5a when exposed to the dialysis membrane. In skin biopsies of patients undergoing dialysis, a significant increase in mast cells has been reported, and it has been suggested that the stimulation and proliferation of mast cells and the release of its mediators, such as histamine, interleukin and proteases, will not be due to CRF, but rather due to the dialysis process (13).…”
Section: Contextmentioning
confidence: 99%
“…As pain and pruritus have similar pattern of activation, acupuncture analgesia is initiated by stimulation, in the muscles of high threshold, small diameter neurons. These nerves send messages to the spinal cord and activates spinal cord, brain stem, and hypothalamic neurons, which triggers endogenous opioid mechanisms [1]. doi: 10.15761/GOD.1000158 Volume 2(6): 218-224…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…The term "uremic pruritus" has been replaced by Patel etal.in the recent times as pruritus in these patients is not directly linked to acute kidney injury. Hence new term has been proposed as "Chronic Kidney Disease" (CKD) associated pruritus [1][2][3][4]. Patients with CKD not only suffer from pruritus but also from other co morbid conditions like drug induced reactions, diabetes mellitus, hypo/hyper thyroidism, lympho proliferative tumours and other neurologic, gastrointestinal and cardiovascular complications which may further complicate the treatment of pruritus [5].…”
Section: Introductionmentioning
confidence: 99%